2004
DOI: 10.1159/000071280
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Progression of Calcific Aortic Stenosis in Dialysis Patients

Abstract: Background: Abnormalities of the aortic valve occur with increased frequency in patients with renal failure and may contribute to the observed excess cardiovascular mortality. Little data exist on the rate at which aortic stenosis progresses in this patient group. Methods: A retrospective case-control study was designed to compare the rate of progression of aortic stenosis in dialysis patients with that in sex-matched controls. Dialysis patients with aortic stenosis were identified by a search of the echocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 15 publications
2
46
0
4
Order By: Relevance
“…To the best of our knowledge, this is the first study to demonstrate that mean visit-to-visit intra-dialytic BP is associated with the progression of AS in CHD patients. The mean yearly progression of AS was 0.18 ± 0.20 cm 2 in our population, which is similar to other studies reporting an accelerated AS progression in CHD patients compared with control patients (0.19 vs. 0.07 cm 2 [7] or 0.14 ± 0.13 vs. 0.06 ± 0.09 cm 2 [8]). We previously reported that SBP accelerates the progression of AS in the same population [11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to demonstrate that mean visit-to-visit intra-dialytic BP is associated with the progression of AS in CHD patients. The mean yearly progression of AS was 0.18 ± 0.20 cm 2 in our population, which is similar to other studies reporting an accelerated AS progression in CHD patients compared with control patients (0.19 vs. 0.07 cm 2 [7] or 0.14 ± 0.13 vs. 0.06 ± 0.09 cm 2 [8]). We previously reported that SBP accelerates the progression of AS in the same population [11].…”
Section: Discussionsupporting
confidence: 91%
“…In CHD patients, aortic valve stenosis (AS), which is associated with cardiovascular atherosclerosis and adverse outcome [3][4][5], is the most important valvular complication contributing to poor prognosis because of its higher prevalence and more rapid progression compared with the general population [6][7][8]. Therefore, the identification of non-traditional and modifiable risk factors affecting AS progression in CHD patients could have a beneficial effect for secondary prevention.…”
Section: Introductionmentioning
confidence: 99%
“…There are significant similarities in clinical risk factors and histopathological alterations between calcific aortic valve disease and coronary atherosclerosis [3]. It is also widely recognized that both cardiac and renal diseases are commonly present in the same patient, and the presence of chronic kidney disease (CKD) further accelerates and amplifies the process of aortic valve calcification via multiple pathways, such as altered mineral metabolism, inflammation, oxidative stress, and pressure and volume overload [4,5]. Previous studies have demonstrated an association between end-stage renal disease and calcific cardiovascular disease, especially in patients on dialysis [6-9]; however, less is known about the impact of early stage CKD on the prevalence and severity of calcific aortic valve disease.…”
Section: Introductionmentioning
confidence: 99%
“…The process of vascular and valvular calcification is accelerated and amplified in patients with chronic kidney disease (CKD) [8,9]. As in the general population, the calcifications observed in CKD patients also appear to indicate a poor prognosis in terms of overall survival and cardiovascular morbidity [10,11,12].…”
mentioning
confidence: 99%